Remittances, Financial Sector Development, Institutions and Economic Growth in the ECOWAS Region - Olaniyan, Temitayo Olumide; Ijaiya, Muftau A.; Kolapo, Funso T. (Migration Letters, 2022)
We investigate the relationship between remittances, financial sector development, institutions, and economic growth in a panel of 15 Economic Community of West African States (ECOWAS) over the period 2000-2017. The empirical evidence is based on the Two-Stage Least Squares Instrumental Variable (2SLS-IV) estimator, which provided two main findings. First, measures of remittances themselves had negative and significant effects on economic growth in the ECOWAS sub-region. The interactive effects of remittances and measures of financial sector development promote growth in the sub-region, thus supporting the complementarity hypothesis. Second, measures of institutional quality had positive and significant effects on the growth of countries in the ECOWAS area. Meanwhile, the interactive terms of remittances and institutional quality show support for the substitutability hypothesis. Therefore, remittances substitute for the presence of weak institutions in the ECOWAS area. Based on the preceding, we suggest the need for ECOWAS countries to further broaden the roles of financial sector institutions inside the remitting process to enhance savings mobilisation and channel the remitted funds into productive and growth-enhancing activities. Moreover, policymakers in ECOWAS countries need to strengthen governance institutions, which could increase the developmental benefits of remittances.